POTENSI ENZIM TRANSGLUTAMINASE SEBAGAI GEL PENYEMBUH LUKA STADIUM II PADA AYAM RAS JANTAN - Sitaresmi Yuningtyas; Winugroho; Abdul Ghoni (Jurnal Farmamedika (Pharmamedika Journal), 2016)
The transglutaminase (EC 2.3.2.13) is an enzyme that catalyses an acyl transfer reaction of the γ-carboxiamide groups glutamine residues in proteins, peptides and various primary amines. Enzyme transglutaminase helps to stabilized the fibrin monomer during the process of blood clotting. This research was to determine the activities of the wound healing process stage II in male broilers given the transglutaminase enzyme sample gels. In this researchgel formulationmadeenzymetransglutaminase1%, 3%, 5% and7%. Transglutaminaseenzymegelpreparationorganoleptictestandhomogeneity test. Furthermore,thegel formulationapplied to themalebroilersownwoundsstage II. Transglutaminaseenzymegel formulationhad ahomogeneoustexture, white, odorlesstypicalenzymetransglutaminase, andhad apH rangefrom 6.2 to 6.7. The percentagereduction inwoundlength ofstage IIinmalebroilersbyenzymetransglutaminaseperfomedgel1%, 3%, 5% , 7% and Bioplacenton® gel (positive control) were 80.54%, 99.00%, 99.67%, 87.25%, and 99.33% respectively. Based on analysis statisticsofANOVA, percentage reduction inwoundlength ofstage IIby treatment withtransglutaminasepreparationgel5% higher and significantly differentcompared totreatmentwithBioplacenton®(positive control). Hence, transglutaminaseenzymepreparations5% gelcanact as awound healerstage IIinmalebroilers.